Why has animal science not led to improved farm animal health and welfare? - Sundrum, Albert (Frontiers in Animal Science, 2024)
Animal science has contributed to a considerable increase in the productive efficiency of animal sourced food. However, livestock farmers have not been able so far to succeed in substantially reducing animal health and welfare problems, which have become an increasingly important issue for consumers with respect to their purchase decision. Before problem solving strategies are considered by farmers, it must be ensured that they do not compromise the economic viability of the farm system. Therefore, promising strategies have to be effective and efficient in the farm specific context, and thus closely aligned to the farm specific causes of animal health and welfare problems. While above all orientation and action-guiding knowledge is needed, the various disciplines of animal science predominantly strive for context-invariant, and thus generalisable disposal knowledge. It is concluded that the predominant approaches of animal science have to be transformed before being able to transform farm systems towards improved animal health and welfare.